Instructional Design Development of Mahilung Mobile Learning Based on the 4-D Model as an Ethno-Edugames Framework for Dayak Cultural Literacy - Maryam Mustika; Eli Karliani; Laila Rahmawati; Widya Karmila Sari Achmad; Karta Jayadi; Firdaus W. Suhaeb; Syahrul (International Journal of Learning Reformation in Elementary Education, 2026)
The implementation of cultural literacy in elementary schools still tends to be content-centric and has not been systematically integrated into digital instructional design, particularly in the context of Dayak culture in Central Kalimantan. This study aims to develop a Mahilung Mobile Learning instructional design based on the 4-D model (Define, Design, Develop, Disseminate) as an ethno-edugames framework in strengthening Dayak cultural literacy in elementary school students. The study uses a Research and Development (R&D) approach with a mixed-methods design. The definition stage includes needs analysis, student characteristics, and curriculum review to identify Dayak cultural values ​​relevant to Theme 8 "Our Friendly Environment." The design stage includes mapping cultural values ​​into learning objectives, game mechanics, and assessment components. The development stage is carried out through the development of an Android-based application prototype that can be accessed offline, equipped with interactive audio-visual materials, exercises, and ten mini-games based on true-false validation with a scoring system as part of the gamification strategy. Expert validation and limited trials were conducted to refine the design. Qualitative data were analyzed thematically, while quantitative data were analyzed using Likert scores to assess feasibility and user response. The results of the study produced a processual ethno-edugames design framework that structurally integrates Dayak cultural values ​​into digital game-based learning. This research contributes to the development of a contextual, adaptive, and applicable culture-based instructional design model in primary education.